A new strain-based finite element for plane elasticity problems. Issue 2 (18th April 2016) - Hamadi, Djamal; Ayoub, Ashraf; Maalem, Toufik
Abstract : Purpose: – The purpose of this paper is to develop a new quadrilateral strain-based element. The element has five nodes, four at the corners as well as an internal node. Design/methodology/approach: – Through the introduction of the internal node, the numerical performance of the element proved to be superior to existing elements in the literature, even though a static condensation is required. Findings: – From several numerical examples, it is shown that convergence can be achieved with the use of only a small number of finite elements. The proposed element can be used to solve general plane linear elasticity problems resulting in excellent results. Originality/value: – The results obtained are comparable with those given by the robust element Q8.